Transcriptional, chromatin, and metabolic landscapes of LDHA inhibitor–resistant pancreatic ductal adenocarcinoma - Malvi, Parmanand; Rawat, Vipin; Gupta, Romi; Wajapeyee, Narendra (Frontiers in Oncology, 2022)
Metabolic reprogramming, due in part to the overexpression of metabolic enzymes, is a key hallmark of cancer cells. Lactate dehydrogenase (LDHA), a metabolic enzyme that catalyzes the interconversion of lactate and pyruvate, is overexpressed in a wide variety of cancer types, including pancreatic ductal adenocarcinoma (PDAC). Furthermore, the genetic or pharmacological inhibition of LDHA suppresses cancer growth, demonstrating a cancer-promoting role for this enzyme. Therefore, several pharmacological LDHA inhibitors are being developed and tested as potential anti-cancer therapeutic agents. Because cancer cells are known to rapidly adapt and become resistant to anti-cancer therapies, in this study, we modeled the adaptation of cancer cells to LDHA inhibition. Using PDAC as a model system, we studied the molecular aspects of cells resistant to the competitive LDHA inhibitor sodium oxamate. We performed unbiased RNA-sequencing (RNA-seq), assay for transposase-accessible chromatin with sequencing (ATAC-seq), and metabolomics analyses of parental and oxamate-resistant PDAC cells treated with and without oxamate to identify the transcriptional, chromatin, and metabolic landscapes of these cells. We found that oxamate-resistant PDAC cells were significantly different from parental cells at the levels of mRNA expression, chromatin accessibility, and metabolites. Additionally, an integrative analysis combining the RNA-seq and ATAC-seq datasets identified a subset of differentially expressed mRNAs that directly correlated with changes in chromatin accessibility. Finally, functional analysis of differentially expressed metabolic genes in parental and oxamate-resistant PDAC cells treated with and without oxamate, together with an integrative analysis of RNA-seq and metabolomics data, revealed changes in metabolic enzymes that might explain the changes in metabolite levels observed in these cells. Collectively, these studies identify the transcriptional, chromatin, and metabolic landscapes of LDHA inhibitor resistance in PDAC cells. Future functional studies related to these changes remain necessary to reveal the direct roles played by these changes in the development of LDHA inhibitor resistance and uncover approaches for more effective use of LDHA inhibitors in cancer therapy.